Analisis Kandungan Logam Berat Kadmium (Cd) pada Gastropoda Conus spp. di Hamparan Lamun Perairan Pesisir Manokwari, Propinsi Papua Barat - Randy Imanuel Sandy Karubuy; Jemmy Manan; Emmanuel Manangkalangi; Luky Sembel; Dandi Saleky (Universitas Diponegoro, 2023)
Manokwari coastal waters are one of the coastal areas that experience very rapid development of development activities from year to year. This condition allows the input of waste such as heavy metal cadmium (Cd) into the waters of Manokwari. This research was conducted in the coastal area of Manokwari (BLK Beach, Lemon Island, and Tanjung Manggewa) for three months (February-April 2020). The purpose of this study was to describe the concentration of heavy metal cadmium (Cd) in Gastropod Conus on the Manokwari Coast and to determine the relationship between heavy metal content of cadmium (Cd) in Conus with shell size, wet weight, and dry weight. Data analysis includes Atomic Absorption Spectrophotometer (AAS), linear regression, and descriptive analysis. Based on the research results obtained, the average content of cadmium in Conus in Manokwari waters is 0.06-0.22 mg/kg. The heavy metal content in Conus is still below the specified threshold so it is still fit for consumption. The relationship between the heavy metal content of Cd in Conus with shell length, wet weight, and dry weight are positive with the regression equation successively y = -0.065 + 0.002x, y = 0.054 + 0.005x, and y = 0.061 + 0.014x which shows that the content Heavy metal Cd in Conus is influenced by shell length, wet weight, and dry weight. Perairan pesisir Manokwari merupakan salah satu wilayah pesisir yang mengalami perkembangan kegiatan pembangunan yang sangat pesat dari tahun ke tahun. Kondisi ini memungkinkan adanya masukan limbah seperti logam berat kadmium (Cd) ke perairan Manokwari. Penelitian ini dilakukan di wilayah pesisir Manokwari (Pantai BLK, Pulau Lemon, dan Tanjjung Manggewa) selama tiga bulan (Februari-April 2020). Tujuan dilakukannya penelitian ini untuk mendeskripsikan konsentrasi logam berat kadmium (Cd) pada Gastropoda Conus di Pesisir Manokwari serta mengetahui hubungan kandungan logam berat kadmium (Cd) dalam Conus dengan ukuran cangkang, berat basah, dan berat kering. Analisis data meliputi Spektrofotometer Serapan Atom (SSA), regresi linear, dan analisis deskriptif. Berdasarkan hasil penelitian yang didapatkan, kandungan rata-rata kadmium pada Conus di perairan Manokwari yaitu sebesar 0,06-0,22 mg/kg. Kandungan logam berat dalam Conus masih dibawah ambang yang ditentukan sehingga masih layak untuk dikonsumsi. Hubungan antara kandungan logam berat Cd dalam Conus dengan panjang cangkang, berat basah dan berat kering adalah positif dengan persamaan regresi berturut-turut y = -0,065 + 0,002x, y = 0,054 + 0,005x dan y = 0,061 + 0,014x yang menunjukan bahwa kandungan logam berat Cd dalam Conus dipengaruhi oleh panjang cangkang, berat basah dan berat kering.